Preventive Management of Covid 19 Using Soap and Hand Sanitizer -A Review. - L, KAVIYA.; ANJALI, A.K; SOMASUNDARAM, JAYALAKSHMI (The journal of contemporary issues in business and government, 2020)
Handwashing is thought to be effective for the prevention of transmission of infectious pathogens. Scientific studies have shown that after hand washing 80 % of individuals retain some pathogenic bacteria on their hands. The purpose of handwashing is to remove potentially harmful organisms from hands preventing the transmission from person to person. Handwashing with non- antibacterial soap and sanitizer was more effective for the removal of bacteria in the prevention of transmission of infectious diseases. Effective handwashing with soap requires reliable access to the quality of water used. The antimicrobial antibacterial, antiviral efficacy of alcohol-based hand sanitizers and soap were compared. The use of soaps for hand hygiene appeared to be less efficacious against Gram-negative organisms. The comparative study addresses the feasibility and health impacts of promoting hand sanitizer as an alternative hand hygiene option for which water- constrained environments should be assessed. However, both hand sanitizers and soaps can be used as effective measures to control the spread of diseases.